Effectiveness study of potential Malay motif particularly floral pattern in jewelry design / Hema Zulaika Hashim - Hashim, Hema Zulaika (2005)
Motif which is used in Malay art decoration can also be applicable in designing of motif for jewelry. The effectiveness ofthe usage of certain motif can be measured according to the request and needs of an individual. This study is intended to show the effectiveness of the potential motif to symbolise identity of Malay jewelry. The intention of the investigation is to look into the appropriateness of the awan larat as a Malay motif in the decoration of the jewelry design. A strong sense of belonging towards dignifying' jewelry identity and the superior being of the Malay race in the Malaysia as seen in the awan larat motif. In designing jewelry, the floral pattern enhances the awan larat decoration. The research has been carried out in the systematic manner which comprises of literature reviews, preparation of the questionnaires, interview respondents and recording of evidences. Additional information in jewelry design is acquired through indepth interview with the jewellers and designers. The usage of Malay motif with traditional concept in designing jewelry indirectly reinforced all designer and related individuals or agencies to involve in the preserving the art of Malay heritage. This study is able to show that the preservation of the Malay motif has a potential and prestige to introduce at international level. In line with this, the design concept ofjewelry is able to portray the originality of identity without the western influence.